Knowledge Management at Cloud Computing Age - De la Hoz Freyle, Javier E.; Carrillo Rincón, Elberto; Gómez Flórez, Luis Carlos (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2012)
Nowadays the most valued asset of the organizations is their knowledge, who is embodiedinto routines, products, services and employees. Knowledge Management arises as a set of strategiessupported by Information Technologies (IT) that tries to leverage the knowledge resources at themaximumlevelto obtaincompetitiveadvantagesthrough newservicesand productscreation,as wellas improving the existing, optimizing the customers relationships, streamlining the time of routinesand serving information and knowledge to the employees on time. The Cloud Computing paradigmdefined by Gartner as: "a computing style where the IT capacities, scalable and elastic, are providedby a service to customers using internet technologies" offers a set of technological advantages to theorganizations that wants to incorporate it in their IT projects. Companies that start knowledge management initiatives, can leverage the Cloud Computing features to maximize the scope of their projects, and in that way obtain advantages among competition. In this paper will be exposed several waysabout how the organizations can upgrade their knowledge management strategies through Cloud Computing features.